GREEN OPERATION STRATEGIES AND SUSTAINABLE OPERATION PERFORMANCE: EXAMINING ROLE OF INFORMATION TECHNOLOGY AS MODERATOR - Hashed Mabkhot; Mukhlisa Usmanova Sagdullayevna (Operational Research in Engineering Sciences: Theory and Applications, 2023)
The research aimed to assess the moderating effect of information technology strategies on the relationship between green operations strategies and sustainable operational performance within pharmaceutical companies in Saudi Arabia. Data were gathered from 282 pharmaceutical companies in Saudi Arabia, utilizing a quantitative deductive approach, and a questionnaire was distributed following a cross-sectional research design. Results obtained through Partial Least Square (PLS)-Structural Equation Modelling (SEM) revealed that all green operations strategies exerted a positive and significant influence on sustainable operational performance. Additionally, moderating effect results indicated that information technology strategy positively and significantly moderates the relationship between green operational strategies and sustainable operational performance. These findings not only empirically validate existing literature but also extend theoretical implications by underscoring the importance of integrating information technology strategies to optimize the impact of green operational strategies within the pharmaceutical industry context. The practical implications are substantial, urging pharmaceutical firms to prioritize effective integration of information technology strategies, thereby fostering data management, process automation, and enhanced supply chain transparency. Furthermore, the research contributes significantly to the field by highlighting the moderating role of information technology strategies. It calls for further exploration into the intricate interactions between information technology strategies and specific green strategies, such as green purchases, green warehouses, and green design within the pharmaceutical industry. This offers a valuable direction for future research and practical implementations.